A randomized clinical study to assess the performance of a marketed denture adhesive in a model of food infiltration in healthy, edentulous adults - Nisha Patel; Roshan Varghese; Gary R. Burnett; Mounir Atassi; Kimberly Milleman; Jeffery Milleman (Wiley, 2023)
Abstract Objectives An optimized food infiltration methodology was utilized to assess the objective and subjective efficacy of a marketed denture adhesive regarding denture dislodgment and infiltration and perception of food particles under maxillary and mandibular dentures. A pilot study helped optimize methodologies before the efficacy study. Materials and Methods Participants were healthy adults (n =48 for both studies) with fair‐ to well‐fitting and well‐made full maxillary and mandibular dentures. In the pilot, groups were a denture adhesive applied in a conventional dabbed‐on pattern, a denture adhesive applied in continuous strips, or no adhesive. In the efficacy study, groups were the Test denture adhesive (continuous strips pattern application) or no adhesive, employed in a crossover design. Food infiltration was investigated through measurement of peanut particle mass retrieved from under each denture (30-32 g chewed). No formal statistical testing was performed in the pilot. Statistical analysis in the efficacy study was performed using analysis of variance. Primary efficacy evaluation was combined peanut particle mass from both dentures. Secondary efficacy evaluations included peanut particle mass under separate dentures, participant‐reported denture dislodgements, and awareness/rates of how bothersome peanut particles under dentures were. Results In the pilot, the median peanut particle mass was lower with either pattern application compared with no adhesive. In the efficacy study, peanut particle mass under combined dentures was lower with than without adhesive (geometric mean [product of values]: 5.56 vs. 29.13 mg) with a between‐group geometric mean ratio (adhesive over no adhesive) of 0.19 (95% confidence interval: 0.12, 0.30) favoring the Test adhesive (p < .0001). Similar Test adhesive beneficial outcomes in both studies included significantly fewer denture dislodgements and awareness and how bothersome peanut particles under dentures were. Treatments were generally well‐tolerated. Conclusions These findings, including reduced peanut particle infiltration, fewer denture dislodgments, and lower ratings of bothersomeness, corroborate those studies investigating the benefits of denture adhesive in preventing food infiltration.